Healthcare workers’ perception of gender and work roles during the COVID-19 pandemic: a mixed-methods study - Henry Thomas Stelfox; Colleen Norris; Jeanna Parsons Leigh; Sofia B Ahmed; Ian D Graham; Harlan Pruden; Valeria Raparelli; Ranjani Somayaji; Louise Pilote; Doreen Rabi; Kirsten Fiest; Patricia Harasym; et al. (BMJ Open)
Objectives A high functioning healthcare workforce is a key priority during the COVID-19 pandemic. We sought to determine how work and mental health for healthcare workers changed during the COVID-19 pandemic in a universal healthcare system, stratified by gender factors.Design A mixed-methods study was employed. Phase 1 was an anonymous, internet-based survey (7 May–15 July 2020). Phase 2 was semistructured interviews offered to all respondents upon survey completion to describe how experiences may have differed by gender identity, roles and relations.Setting National universal healthcare system (Canada).Participants 2058 Canadian healthcare worker survey respondents (87% women, 11% men, 1% transgender or Two-Spirit), including 783 health professionals, 673 allied health professionals, 557 health support staff. Of the 63 unique healthcare worker types reported, registered nurses (11.5%), physicians (9.9%) and pharmacists (4.5%) were most common. Forty-six healthcare workers were interviewed.Main outcome measures Reported pandemic-induced changes to occupational leadership roles and responsibilities, household and caregiving responsibilities, and anxiety levels by gender identity.Results Men (19.8%) were more likely to hold pandemic leadership roles compared with women (13.4%). Women (57.5%) were more likely to report increased domestic responsibilities than men (45%). Women and those with dependents under the age of 10 years reported the greatest levels of anxiety during the pandemic. Interviews with healthcare workers further revealed a perceived imbalance in leadership opportunities based on gender identity, a lack of workplace supports disproportionately affecting women and an increase in domestic responsibilities influenced by gender roles.Conclusions The COVID-19 pandemic response has important gendered effects on the healthcare workforce. Healthcare workers are central to effective pandemic control, highlighting an urgent need for a gender-transformative pandemic response strategy.